THE CHANGES IN INPUT-COEFFICIENTS - F. H. Omar B.S.C (Dirasat in Economics and Business, 1969)
The stability of input-output coefficients over time can be considered under certain theoretical conditions. The simple input- output model in which the input coefficients are stable over time is constructed assuming the following: 1. The technique of production remains the same over time. 2. The inputs purchased by each industry are proportional to the level of output of that industry. 3. The output of each industry is a homogeneous commodity, and there is only one production function by which it can be produced. Joint production by an industry of a commodity also produced in another industry does not exist; otherwise the inputs absorbed by a given output would depend on the varying combination of two produc- tion functions of two industries.